Unraveling the Geodynamic Evolution of the Pre– and Early–Andean Margin: Insights From Numerical Modeling - Harim Arvizu; Vlad Constantin Manea; Verónica Oliveros; Paulina Vásquez (Geophysical Research Letters)
Abstract An outstanding question in the geological evolution of the Chilean Andes is the cause of the westward shift and relocation of magmatism from the High Andes (HA) to the Coastal Cordillera (CC) during the Late Triassic, Pre–Andean stage. The spatiotemporal distribution of Permian–Triassic–Jurassic igneous rocks in northern‐central Chile (20°S–32°S) reveals a significant westward magmatic shift of ∼120 km during the Norian time. Despite diverse proposed models, the precise geodynamic mechanism behind this shift remains unclear. To address this, we used 2D numerical modeling to investigate two contrasting scenarios: (a) subduction rollback and (b) subduction transference/jump and reinitiation by terrane accretion. Our modeling results strongly support Scenario B, where mantle density and the size of the oceanic plateau are crucial for triggering subduction jump and reinitiation. This model aligns with geological and geophysical evidence and offers new insights into unraveling the Pre– and Early–Andean evolution.